Isobavachalcone ameliorates Alzheimer disease pathology by autophagy-mediated clearance of amyloid beta and inhibition of NLRP3 inflammasome in primary astrocytes and 5x-FAD mice - Kour, Dilpreet; Khajuria, Parul; Sharma, Kuhu; Sharma, Alpa; Sharma, Ankita; Ali, Syed Mudassir; Wazir, Priya; Ramajayan, P.; Sawant, Sanghapal D.; Nandi, Utpal; Ahmed, Zabeer; Kumar, Ajay (Frontiers in Pharmacology, 2025)
Background and Aim Alzheimer's disease (AD) progresses with A beta plaque deposition and neuroinflammation. Given the complexity of AD pathology, single-target therapies have frequently failed in clinical trials. We hypothesized that a multitarget approach could yield better therapeutic outcomes. To this end, we identified isobavachalcone (IBC), a natural compound with dual pharmacological activity in reducing A beta plaques and neuroinflammation.Experimental Procedure Primary astrocytes were isolated from 3 to 4 days old C57BL/6J mice pups for in-vitro assays, while in-vivo studies were conducted on 5x-FAD mice. Protein alterations were evaluated using ELISA, western blotting, immunocytochemistry, and immunohistochemistry. Behavioral analyses included the radial arm maze, open field, and rotarod tests. Data from all in vitro and in vivo experiments were analyzed by using one-way ANOVA and post-hoc Bonferroni tests.Results In-vitro analyses in astrocytes demonstrated that IBC at 5 and 10 mu M concentrations induce AMPK phosphorylation through CAMKK2, promoting autophagy and inhibiting the NLRP3 inflammasome in primary astrocytes. IBC-treated astrocytes exhibited significant clearance of extracellular amyloid beta. Mechanistic studies highlighted autophagy as a key factor in reducing both NLRP3 inflammasome activity and A beta levels. Two months of treatment of 5x-FAD mice with IBC at 25 and 50 mg/kg significantly improved cognitive functions, as evidenced by enhanced memory and motor performance in behavioral tests. Subsequent brain tissue analysis revealed that IBC upregulated autophagic proteins to reduce the brain's amyloid beta levels, resulting in decreased expression of neuroinflammation markers.Conclusion IBC effectively ameliorates AD pathology through autophagy-mediated clearance of A beta and suppressing neuroinflammation in 5x-FAD mice.
Keywords: Alzheimer disease; Amyloid beta; Autophagy; isobavachalcone; neuroinflammation; NLRP3 inflammasome